Where the lost wander : a novel - Harmon, Amy (Lake Union Publishing, 2020)
The Overland Trail, 1853: Naomi May never expected to be widowed at twenty. Eager to leave her grief behind, she sets off with her family for a life out West. On the trail, she forms an instant connection with John Lowry, a half-Pawnee man straddling two worlds and a stranger in both. But life in a wagon train is fraught with hardship, fear, and death. Even as John and Naomi are drawn to each other, the trials of the journey and their disparate pasts work to keep them apart. John's heritage gains them safe passage through hostile territory only to come between them as they seek to build a life together. When a horrific tragedy strikes, decimating Naomi's family and separating her from John, the promises they made are all they have left. Ripped apart, they can't turn back, they can't go on, and they can't let go. Both will have to make terrible sacrifices to find each other, save each other, and eventually...make peace with who they are.